China on the international area and doctrine of «peaceful rising» (Journal of Oriental Studies, 2016)
the article examines the main directions of the new development strategy of China in the international area, showing the characteristics of the implementation of “peaceful rise” in practice, and analyzing the main course of the PrC leadership in foreign policy-rejection of hegemony and domination in the world
Keywords: foreign policy; «peaceful rise»